Analisis Dinamika Arus Barang dan Penumpang di Pelabuhan Laut Kabupaten Wakatobi dan Keterkaitannya dengan Sektor Transportasi Regional - Rizal, Rizal; Harjun, Harjun; Muh Syata, Wahyu; M Hubaib, Ilhamurrahman (Teewan Journal Solutions, 2026)
Indonesia's development, as an archipelagic country, has important seaport centers that theoretically should drive regional economic growth. The study aims to analyze the influence of the volume of goods flow (X1) and the number of passengers (X2) on the Gross Regional Product (GDP) of the transportation and warehousing sector (Y) in Wakatobi Regency (in the period 2020–2024) and simultaneously test the hypothesis of the leakage phenomenon. The method used is a quantitative method with multiple linear regression (OLS) analysis on monthly time series data. The results of the F test show that X1 and X2 simultaneously have a significant influence on Y, with an explanatory power of 75.1% (Adj. R² = 0.751). However, the results of the partial t test reveal important contradictory findings: The Volume of Goods Flow (X1) has a positive and significant influence on Y (coefficient +0.981), confirming that logistics activities are successful in generating local added value. Passenger Volume (X2) has a negative and significant influence on Y (coefficient -0.255). These findings confirm the existence of Economic Leakage. Despite very high passenger volumes (reaching 165,628 people in 2024), Wakatobi's transportation sector GDP actually experienced negative growth (-3.69% in 2024), as most of the added value from passenger transportation services was recorded outside Wakatobi by non-local operators.